Análise comparativa de correlações para o fator de atrito interfacial em escoamentos gás-líquido no padrão anular em tubulações - Paula Junior, Cidelei Ferreira de (2015)
The two-phase flow is a flow of two diferente componentes or phases. This flow may be an anular flow where one phase or componente flows forming a film layer over the other phase or component. The two-phase flow may be presente on disposal suffering boiling or condensation, for example, steam generation or cooling the petroleum industry. The anular flow is essential that the interfacial friction fator between the phases is known, so that through interfacial shear stress can be calculated differential pressure, forces and pressure drop, so being able to scale the equipment for a given flow. To calculate the interfacial friction fator diferente authors have proposed diferente correlations interfacial friction factors. The work is to compare the results of the correlations to calculate the interfacial friction fator in two-phase flow anular tube. Through experimental data were performed so comparative calculations of interfacial friction factors proposed by the authors with the measured interfacial factors, obtained from the literature. Were contacted to the constraints that each method is to quantify the methods best accuracies, experimental data used of the anular flow transitional. The comparison has a wide and clear, using methods to quantify the final resuts, demonstrating what methods are more accurate compared to the experimental data used.